Transmittance variable optical laminate and manufacturing method therefor, and smart window including the same
The variable transmittance optical laminate with an ultraviolet blocking base material and protection layer addresses the issue of fixed transmittance and ultraviolet-induced deterioration, enhancing the durability and performance of smart windows.
Patent Information
- Application Number
- JP2024095001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-13
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-25
AI Technical Summary
Conventional glass windows and external light blocking coatings have fixed transmittance, leading to issues such as glare during the day and reduced visibility at night, and they do not efficiently block ultraviolet rays, which can cause deterioration of liquid crystal layers in variable transmittance optical laminates.
A variable transmittance optical laminate with a first polarizing plate containing an ultraviolet blocking base material, a polarizer, and a near ultraviolet protection layer, along with transparent conductive layers, is designed to block ultraviolet rays and prevent deterioration of the liquid crystal layer.
The laminate effectively blocks ultraviolet rays, preventing deterioration of the liquid crystal layer and improving the longevity of the smart window, while maintaining transparency and reducing glare.
Smart Images

Figure 2024178934000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a variable transmittance optical laminate, a method for producing the same, and a smart window including the same. [Background technology]
[0002] In general, an external light blocking coating is often applied to glass windows of vehicles and other means of transportation. However, the glass windows of conventional means of transportation have a fixed transmittance, and the external light blocking coating also has a fixed transmittance. Therefore, the windows of such conventional means of transportation have a fixed overall transmittance, which may lead to accidents. For example, if the overall transmittance is set low, there is no problem during the day when there is sufficient light around, but at night when there is insufficient light around, there is a problem that the driver and others have difficulty in properly checking the surroundings of the means of transportation. Alternatively, if the overall transmittance is set high, there is a problem that the driver and others may be dazzled during the day when there is sufficient light around. In addition, an external light blocking coating is often applied to glass windows of buildings and the like for the efficiency of heating and cooling and energy saving. In this case, if the transmittance is fixed, there is a problem that it is not efficient in energy saving, just like in the case of means of transportation.
[0003] As a result, a variable transmittance optical laminate was developed that can change the transmittance of light when a voltage is applied. The variable transmittance optical laminate is driven by applying a voltage to drive liquid crystals to change the transmittance, and the desired transmittance is achieved by providing a liquid crystal layer whose phase changes when an electric field is applied to change the transmittance. However, near-ultraviolet rays and ultraviolet rays are transmitted to the liquid crystal of the variable transmittance optical laminate, which frequently causes problems with deterioration of the liquid crystal layer, thereby shortening the lifespan of the display.
[0004] Meanwhile, Korean Patent Publication No. 10-0416924 relates to a method for imparting ultraviolet absorbing properties to a polarizing film using a polyvinyl alcohol film as a substrate and a polarizing film having ultraviolet absorbing properties manufactured by the method, but when applied to liquid crystal display devices and smart windows including polarizing plates, there is a limit to preventing deterioration due to ultraviolet rays and controlling transmittance even after voltage application.
[0005] Therefore, there is a need to develop a variable transmittance optical laminate that includes a polarizing plate and has excellent light resistance by lowering the transmittance when a voltage is applied, and a smart window including the same. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Registration No. 10-0416924 Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above-mentioned problems, the present invention aims to provide a variable transmittance optical laminate that has excellent light resistance, maintains transparency in the visible light region, and can efficiently block near-ultraviolet rays to prevent deterioration of the liquid crystal layer.
[0008] The present invention also provides a smart window including the variable transmittance optical laminate, and a vehicle or building fixture using the smart window.
[0009] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0010] The present invention relates to a variable transmittance optical laminate comprising a first polarizing plate, a first transparent conductive layer formed on one side of the first polarizing plate, a second polarizing plate facing the first polarizing plate, a second transparent conductive layer formed on one side of the second polarizing plate and facing the first transparent conductive layer, and a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer, wherein the first polarizing plate comprises an ultraviolet blocking substrate, a polarizer, and a near ultraviolet protective layer.
[0011] In the present invention, the first polarizing plate may be formed on an outer surface facing a light source. The present invention may be characterized in that the first polarizing plate has an ultraviolet blocking substrate, a polarizer, and a near ultraviolet protection layer laminated in this order from an outer surface facing a light source.
[0012] The present invention may be characterized in that the ultraviolet ray blocking substrate has a transmittance of 10% or less at a wavelength of 380 nm or less.
[0013] The present invention may be characterized in that the ultraviolet blocking substrate contains an ultraviolet blocking additive.
[0014] The present invention may be characterized in that the ultraviolet blocking substrate includes at least one selected from the group consisting of a polyester film, a cellulose film, a polyimide film, and a polycarbonate film.
[0015] In the present invention, the near ultraviolet protection layer may contain one or more selected from a near ultraviolet absorber and an ultraviolet light enhancer / reducer.
[0016] The present invention may be characterized in that the near ultraviolet absorbent has a maximum absorption wavelength of 390 nm to 430 nm.
[0017] The present invention may be characterized in that the near ultraviolet absorbing agent is a cyanine compound.
[0018] In the present invention, the ultraviolet light enhancer may have a maximum absorption wavelength of 350 nm to 400 nm.
[0019] The present invention may be characterized in that the ultraviolet light enhancer is an oxazole compound.
[0020] In the present invention, at least one of the first polarizing plate and the second polarizing plate may include one or more functional layers selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
[0021] In the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0022] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with either one of the first polarizing plate and the second polarizing plate without the inclusion of a separate substrate between the transparent conductive layer and either one of the first polarizing plate and the second polarizing plate.
[0023] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may further include an easy-adhesion layer between the transparent conductive layer and one of the first polarizing plate and the second polarizing plate, and may be formed in direct contact with the transparent conductive layer.
[0024] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may contain one or more materials selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0025] In the present invention, the liquid crystal layer may include one or more spacers selected from the group consisting of a ball spacer and a column spacer.
[0026] In the present invention, the variable transmittance optical laminate may further include one or more layers selected from the group consisting of a sealant, an alignment film, an adhesive layer, and an ultraviolet absorbing layer.
[0027] The present invention also relates to a method for producing the variable transmittance optical laminate. The present invention also relates to a smart window comprising the variable transmittance optical laminate.
[0028] The present invention may also relate to a means of transportation including the smart window, and may also relate to an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
[0029] The present invention may also relate to a wearable device, a building fixture, and the like, that includes the smart window. Effect of the Invention
[0030] The variable transmittance optical laminate of the present invention has low transmittance in the ultraviolet and / or near ultraviolet region, and therefore can effectively block ultraviolet and / or near ultraviolet rays, thereby preventing deterioration of the liquid crystal layer caused by ultraviolet rays and improving the problem of shortened display lifespan.
[0031] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the thickness can be significantly reduced compared to conventional optical laminates.
[0032] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the transmittance in the light transmission mode can be improved compared to conventional optical laminates.
[0033] In addition, by including the variable transmittance optical laminate according to the present invention, a high-quality smart window and a vehicle or building fitting using the same can be provided. [Brief description of the drawings]
[0034] [Figure 1] FIG. 1 shows the structure of a first polarizing plate according to an embodiment of the present invention. [Diagram 2] FIG. 2 shows a preferred layer structure of a variable transmittance optical layered body according to an embodiment of the present invention. [Figure 3a] 3a to 3c show the light resistance evaluation observation results of the experimental examples, respectively. Specifically, FIG. 3a shows a state in which no light leakage phenomenon was observed and opacity was maintained. [Figure 3b] FIG. 3b shows a state where light leakage is partially observed. [Figure 3c] FIG. 3c shows a state where the light leakage phenomenon is observed over the entire surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The present invention relates to a variable transmittance optical laminate capable of effectively blocking ultraviolet and / or near ultraviolet rays to prevent deterioration of a liquid crystal layer caused by ultraviolet rays, a manufacturing method thereof, and a smart window including the same. More specifically, the variable transmittance optical laminate includes a first polarizing plate, a first transparent conductive layer formed on one surface of the first polarizing plate, a second polarizing plate facing the first polarizing plate, a second transparent conductive layer formed on one surface of the second polarizing plate and facing the first transparent conductive layer, and a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer, and the first polarizing plate includes an ultraviolet blocking substrate, a polarizer, and a near ultraviolet protective layer, and preferably, the first polarizing plate may be characterized in that the ultraviolet blocking substrate, the polarizer, and the near ultraviolet protective layer are sequentially stacked from an outer surface facing a light source.
[0036] According to one embodiment of the present invention, the laminate film may be characterized by a low transmittance of 10% or less at 360 nm wavelength, 380 nm wavelength and / or 400 nm wavelength, preferably 9% or less, more preferably 7% or less. In this case, it is possible to effectively block ultraviolet and / or near ultraviolet rays, thereby preventing deterioration of the liquid crystal layer, and thereby provide a high-quality smart window and automotive or building fittings using the same.
[0037] The variable transmittance optical laminate of the present invention is particularly suitable for technical fields in which light transmittance can be changed by applying a voltage, and can be used, for example, in smart windows.
[0038] A smart window is an optical structure that controls the amount of light or heat passing through by changing the light transmittance according to the application of an electrical signal. That is, a smart window is designed to be able to change to a transparent, opaque, or translucent state according to voltage, and is also called variable transmittance glass, light control glass, or smart glass.
[0039] Smart windows can be used as partitions for dividing or protecting privacy in the interior spaces of vehicles and buildings, or as daylight windows placed in the openings of buildings. They can also be used as highway signs, bulletin boards, odometer signs, clocks, or advertising screens, and can be used to replace glass in vehicles such as windows or sunroofs in cars, buses, airplanes, ships, or trains.
[0040] The variable transmittance optical laminate of the present invention can also be used in smart windows in many of the above-mentioned technical fields, but since the conductive layer is directly formed on the polarizing plate, no separate substrate is required for forming the conductive layer, and therefore the thickness is thin and the bending characteristics are advantageous, making it particularly suitable for use in smart windows for vehicles or buildings. In one or more embodiments, the smart window to which the variable transmittance optical laminate of the present invention is applied can be used as a front window, rear window, side window, and sunroof window of an automobile, or a building fixture, and can be used not only for blocking external light, but also for dividing the interior space of an automobile or building, such as an interior partition, or for privacy protection.
[0041] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the following drawings attached to this specification are only for illustrating preferred embodiments of the present invention and serve to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned content of the invention, and therefore the present invention should not be interpreted as being limited only to the matters shown in these drawings.
[0042] The terms used in this specification are for the purpose of describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the phrase. For example, the term "polarizer" used in this specification may mean at least one polarizer of the first polarizer and the second polarizer, and the term "transparent conductive layer" may mean at least one transparent conductive layer of the first transparent conductive layer and the second transparent conductive layer.
[0043] As used herein, "comprises" and / or "comprising" are used in a sense that does not exclude the presence or addition of one or more other components, steps, operations and / or elements other than the stated components, steps, operations and / or elements. The same reference numerals refer to the same components throughout the specification.
[0044] Spatially relative terms such as "below," "bottom," "lower," "upper," "top," and the like, may be used to easily describe the relationship of one element or component to another element or component as depicted in the drawings. Spatially relative terms should be understood to include different orientations of elements in use or operation in addition to the orientation depicted in the drawings. For example, if an element depicted in the drawings is turned upside down, an element described as "below" or "below" another element may be placed "above" the other element. Thus, the exemplary term "below" can include both an orientation of below and above. Elements may be oriented in other directions, and thus the spatially relative terms may be interpreted accordingly.
[0045] In the present invention, "transparent" means that the transmittance of visible light is 70% or more, or 80% or more.
[0046] In the present invention, "ultraviolet rays" refers to rays having a wavelength of 100 to 390 nm, and "near ultraviolet rays" refers to rays having a wavelength of 390 to 420 nm.
[0047] In the present invention, the terms "shielding" and "blocking" are used substantially indistinguishably to mean preventing the influence of light such as ultraviolet light or near ultraviolet light.
[0048] Referring to Figures 1 and 2, the term "outer surface" used in this specification refers to the surface facing the direction (A) in which the light source is incident, and means the surface that is directly affected by light rays such as ultraviolet rays or near ultraviolet rays.
[0049] <Variable transmittance optical laminate> FIG. 1 shows the structure of a first polarizer according to an embodiment of the present invention, and FIG. 2 shows a preferred laminate structure of a variable transmittance optical laminate according to an embodiment of the present invention. Referring to FIG. 2, the variable transmittance optical laminate 100 of the present invention relates to a variable transmittance optical laminate including a first polarizer 110-1, a first transparent conductive layer 120-1 formed on one surface of the first polarizer, a second polarizer 110-2 facing the first polarizer, a second transparent conductive layer 120-2 formed on one surface of the second polarizer and facing the first transparent conductive layer, and a liquid crystal layer 130 provided between the first transparent conductive layer and the second transparent conductive layer. Referring to FIG. 1, the first polarizer 110-1 may include an ultraviolet blocking substrate 111, a polarizer 112, and a near ultraviolet protection layer 113, and may further include a protective layer (protective film, not shown).
[0050] First polarizing plate 110-1 1 and 2, a variable transmittance optical laminate according to an embodiment of the present invention includes a first polarizing plate 110-1 formed on an outer surface facing a light source A, and the first polarizing plate 110-1 may include an ultraviolet blocking substrate 111, a polarizer 112, and a near ultraviolet protection layer 113. More specifically, as shown in FIG. 1, it is more preferable that the ultraviolet blocking substrate 111, the polarizer 112, and the near ultraviolet protection layer 113 are sequentially laminated from the outer surface facing the light source A in order to manufacture a polarizing plate using an ultraviolet curing adhesive and prevent contamination of the liquid crystal layer due to bleed-out of an absorbent.
[0051] Specifically, when the ultraviolet absorber and the near-ultraviolet absorber are mixed together in the same substrate layer, there is a risk of contamination of adjacent layers due to bleed-out of the absorber, so it is preferable to add them separately in separate layers. Meanwhile, in the case where a UV-curable adhesive is used for bonding the polarizer protection film in addition to the need to protect the polarizer from UV rays, UV irradiation must be performed sufficiently to cure the adhesive, so UV transmission is required on at least one side based on the polarizer. Therefore, as shown in FIG. 1, the transmittance variable optical laminate according to the stacking sequence of one embodiment of the present invention is considered to be an optimized stacking sequence that prevents UV deterioration of the polarizing layer and the liquid crystal layer while simultaneously preventing contamination through bleed-out of the absorber, in addition to the purpose of manufacturing a structure using a UV-curable adhesive.
[0052] UV-blocking base material 111 According to one embodiment of the present invention, the first polarizer 110-1 includes an ultraviolet blocking substrate 111, which has an ultraviolet blocking function and is preferably formed on an outer surface facing the direction in which the light source is incident (A in Figs. 1 and 2) in order to protect both the polarizing layer and the liquid crystal layer from ultraviolet rays. Specifically, by including the ultraviolet blocking substrate, a transmittance of 10% or less at a wavelength of 380 nm is preferable in order to effectively protect the polarizing layer and the liquid crystal layer from ultraviolet rays, specifically ultraviolet rays and near ultraviolet rays, and can effectively block wavelengths in the ultraviolet range to ensure the hardness of the coating layer. The ultraviolet blocking substrate of the present invention includes an ultraviolet blocking additive and has an ultraviolet blocking function.
[0053] In addition to the UV blocking function, the UV blocking substrate 111 may also function to prevent damage to the inner substrate when damage such as impact, scratch, etc. is applied to the laminate and / or the front surface of the smart window including the same, by absorbing the impact. For this reason, a material having a high tolerance to deformation energy is preferable, and examples thereof include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate; polyimide-based resins; acrylic-based resins; styrene-based resins such as polystyrene and acrylonitrile-styrene; polycarbonate-based resins; polylactic acid resins; polyurethane-based resins; polyolefin-based resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl-based resins such as polyvinyl chloride and polyvinylidene chloride; polyamide-based resins; sulfone-based resins; polyether-ether ketone-based resins; arylate-based resins; cellulose-based resins such as triacetyl cellulose, or release films formed from mixtures of the above resins. In particular, the protective film may include at least one selected from polyester-based films, cellulose-based films, polyimide-based films, and polycarbonate films, and in one embodiment of the present invention, a cellulose-based film is most preferred because it is optically transparent and has excellent resistance to friction, heat, and / or chemical damage. The thickness of the substrate using the cellulose-based resin can be applied without any restrictions, but the thicker the substrate, the heavier it is and the less easy it is to handle, so a thickness of 25 to 80 μm is preferred as a protective film.
[0054] According to one embodiment of the present invention, the UV-blocking substrate includes a UV-blocking additive and has a UV-blocking function. When the substrate includes a UV-blocking additive, the substrate can effectively block UV rays in the region of 400 nm or less, prevent deterioration of the liquid crystal layer, and improve the problem of shortened life of the variable transmittance optical laminate and the smart window including the same. The UV-blocking additive may be, but is not limited to, a benzophenone compound, a benzotriazole, or a triazine-based compound, and is preferably included in an amount of 0.1% to 10% based on the total weight of the composition forming the substrate.
[0055] The thickness of the UV blocking substrate 111 is not particularly limited and may be, for example, 10 to 100 μm. When the thickness is within the above range, it is easy to handle and is preferable as a member of a smart window laminate.
[0056] Polarizer 112 In the variable transmittance optical laminate according to an embodiment of the present invention, at least one of the first polarizer 110-1 and the second polarizer 110-2 may be a conventional or later developed polarizer, and preferably, in the case of the first polarizer 110-1, the UV blocking substrate 111, the polarizer 112, and the near UV protection layer 113 described below may be sequentially laminated. The polarizer may be, for example, a stretched polarizer or a coated polarizer.
[0057] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA)-based resin. The polyvinyl alcohol (PVA)-based resin may be a polyvinyl alcohol-based resin obtained by saponifying a polyvinyl acetate-based resin. Examples of the polyvinyl acetate-based resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. The other monomers may be unsaturated carboxylic acid-based, unsaturated sulfonic acid-based, olefin-based, vinyl ether-based, and acrylamide-based monomers having an ammonium group. The polyvinyl alcohol (PVA)-based resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes.
[0058] In an embodiment, the coating type polarizer may be formed by a liquid crystal coating composition, and the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.
[0059] The reactive liquid crystal compound can be similarly applied to the reactive liquid crystal compound of the optically functional film described above.
[0060] The dichroic dye is a component contained in the liquid crystal coating composition to impart polarization properties, and has a property that the absorbance in the long axis direction of the molecule is different from that in the short axis direction. The dichroic dye may be a dichroic dye that has been used or will be developed in the future, and may include, for example, an acridine dye, an oxazine dye, a cyanine dye, a naphthalene dye, an azo dye, an anthraquinone dye, etc., which may be used alone or in combination.
[0061] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, and may include, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. Also, the liquid crystal coating composition may further include a labeling agent, a polymerization initiator, etc., within a range that does not inhibit the polarization properties of the coating film.
[0062] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, and may include, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. Also, the liquid crystal coating composition may further include a labeling agent, a polymerization initiator, etc., within a range that does not inhibit the polarization properties of the coating film.
[0063] The coating layer may have an elastic modulus of 10 MPa or more, preferably 10 to 10 4 When the elastic modulus of the coating layer satisfies the above range, it can exhibit excellent adhesion and flexibility.
[0064] In an embodiment, the coating layer may be formed of a photocurable coating layer forming composition including a photopolymerizable compound and a photopolymerization initiator.
[0065] The photopolymerizable compound is not particularly limited as long as it allows the coating layer to exhibit the elastic modulus range described above, and for example, acrylic monomers, epoxy monomers, vinyl ether monomers, oxetane monomers, etc. may be used, and from the viewpoint of improving the elastic modulus, epoxy monomers, vinyl ether monomers, and oxetane monomers may be preferably used. These may be used alone or in combination of two or more kinds.
[0066] Examples of the acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, (meth)acrylate, 2-methoxyethyl (meth)acrylate, (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, Glycerol mono(meth)acrylate, 3-chloro-2-hydroxypropyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, isobornyl (meth)acrylate, N-vinylpyrrolidone, acryloylmorpholine, urethane (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, (meth)acrylate of mono-ε-caprolactone adduct of tetrahydrofurfuryl alcohol, (meth)acrylate of di-ε-caprolactone adduct of tetrahydrofurfuryl alcohol, (meth)acrylate of mono-ε-methyl-δ-valerolactone adduct of tetrahydrofurfuryl alcohol, (meth)acrylate of di-β-methyl-δ-valerolactone adduct of tetrahydrofurfuryl alcohol, ω-carboxy-polycaprolactone monoacrylate, dimethylaminoethyl acrylate, and the like. These may be used alone or in combination of two or more.
[0067] Examples of the epoxy monomer include aromatic epoxy compounds, alicyclic epoxy compounds, and aliphatic epoxy compounds.
[0068] Examples of the aromatic epoxy compound include diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and phenoxyglycidyl ether.
[0069] Examples of the alicyclic epoxy compound include dicyclopentadiene dioxide, limonene dioxide, 4-vinylcyclohexene dioxide, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate, and bis(3,4-epoxycyclohexylmethyl)adipate.
[0070] Examples of the aliphatic epoxy compound include 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, and polytetramethylene glycol diglycidyl ether.
[0071] Examples of the vinyl ether monomer include diethylene glycol divinyl ether, triethylene glycol divinyl ether, cyclohexyl vinyl ether, polyethylene glycol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, etc. These may be used alone or in combination of two or more.
[0072] Examples of oxetane monomers include 2-ethylhexyloxetane, xylene bisoxetane, 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyloxetan-3-yl)methoxymethyl]benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, bis(3-ethyl-3-oxetanylmethyl)ether, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, phenol novolac oxetane, 1,3-bis[(3-ethyloxetan-3-yl)methoxy]benzene, etc. These may be used alone or in combination of two or more.
[0073] The photopolymerization initiator may be a cationic initiator or a radical initiator that is commonly used in the art. Examples of the cationic initiator include an onium salt compound and an iron-allene complex.
[0074] The onium salt compound may be, for example, an aromatic diazonium salt such as benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, or benzenediazonium hexafluoroborate; an aromatic iodonium salt such as diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, or di(4-nonylphenyl)iodonium hexafluorophosphate; triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, 4,4'-bis[diphenylsulfonio]diphenylsulfide bishexafluorophosphate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonium 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenylsulfide bishexafluorophosphate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonio -diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonio-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluyl)sulfonio-diphenyl sulfide tetrakis(pentafluorophenyl)borate, aromatic sulfonium salts such as diphenyl[4-(phenylthio)phenyl]sulfonium phosphate; and the like.
[0075] Examples of the iron-allene complex include xylene-cyclopentadienyliron(II) hexafluoroantimonate, cumene-cyclopentadienyliron(II) hexafluorophosphate, and xylene-cyclopentadienyliron(II)-tris(trifluoromethylsulfonyl)methanide.
[0076] The radical initiator may be an acetophenone-based, benzoin-based, benzophenone-based, thioxanthone-based, triazine-based compound, etc. These may be used alone or in combination of two or more kinds.
[0077] Examples of the acetophenone-based compound include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-[2-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one.
[0078] Examples of the benzoin-based compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0079] Examples of the benzophenone-based compounds include benzophenone, methyl o-benzoin benzoate, 4-phenylbenzophenone, 4-benzoin-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0080] Examples of the thioxanthone compound include 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone.
[0081] Examples of the triazine-based compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-piperonyl-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2 -(5-methylfuran-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine, and the like.
[0082] The content of the photopolymerization initiator is not particularly limited, and may be, for example, 0.1 to 10 parts by weight based on 100 parts by weight of the photopolymerizable compound. When the content is within the above range, it can be cured to an appropriate level to form a coating layer exhibiting the above elastic modulus range.
[0083] In one or more embodiments, the thickness of the coating layer may be 3 to 10 μm, and more preferably 3 to 7 μm. If the thickness of the coating layer is less than 3 μm, the cohesive strength and elastic modulus may be low or it may be difficult to exhibit adhesion, particularly the adhesion between the polarizer and the coating layer may be reduced, and the function of protecting the polarizer may be reduced. In addition, if the thickness of the coating layer exceeds 10 μm, a phase difference may occur, making it difficult to control the transmittance, and in particular the adhesion between the conductive layer and the coating layer may be reduced, making it difficult to form the conductive layer.
[0084] In an embodiment, the coating layer may further include nanoparticles to improve the hardness and adhesion of the coating layer.
[0085] In one embodiment, at least one of the first polarizing plate 110-1 and the second polarizing plate 110-2 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm. In this case, at least one of the first polarizing plate 110-1 and the second polarizing plate 110-2 maintains optical properties, and a thin optical laminate can be manufactured.
[0086] At least one of the first polarizer 110-1 and the second polarizer 110-2 may have a curved shape in order to manufacture an optical laminate having a curved surface, for example, it may be formed in a curved shape toward one of two different polarizers 110-1 and 110-2 stacked on both sides of the liquid crystal layer 130.
[0087] Near UV protection layer 113 The near-ultraviolet protection layer 113 of the present invention is formed on one side of the polarizer 112 of the first polarizing plate 110-1 to protect the polarizer, and may be preferably located on the inner side not directly facing the light source A. In this case, there is an advantage in that bleed-out is prevented and the liquid crystal layer is protected. The near-ultraviolet protection layer 113 may include a near-ultraviolet absorber having a maximum absorption wavelength of 390 nm to 430 nm, and may be formed by applying a composition on the polarizer and curing it by UV irradiation. Specifically, the near-ultraviolet protection layer 113 may transmit ultraviolet light and selectively absorb near-ultraviolet light by including at least one selected from a near-ultraviolet absorber and an ultraviolet light enhancer and may further include a composition for forming a hard coating layer commonly used in the technical field to which the present invention belongs, such as a photocurable resin, an initiator, and a solvent labeling agent. In addition, the content thereof is not particularly limited since it can be variously adjusted within a range that does not deteriorate the physical properties of the variable transmittance optical laminate according to the present invention.
[0088] The near-ultraviolet ray absorbent transmits ultraviolet rays and selectively absorbs near-ultraviolet rays. The near-ultraviolet ray absorbent according to an embodiment of the present invention may have a maximum absorption wavelength of 390 nm to 430 nm, preferably 395 nm to 425 nm, and more preferably 400 nm to 420 nm. The near-ultraviolet ray absorbent may be, for example, at least one selected from cyanine, benzophenone compounds, benzotriazole, and triazine-based compounds, and is most suitable for effectively absorbing near-ultraviolet rays in the 390 nm to 430 nm range when it is a cyanine-based derivative. In general, in the case of a display, 380 nm is set as the upper boundary value for blocking ultraviolet rays in order to transmit the short wavelength region (blue) of visible light. However, since the present invention is a smart window laminate whose main function is to block or transmit external light (sunlight), it is relatively insensitive to hue changes due to partial blocking of the visible light region, and therefore has the advantage of being able to effectively prevent deterioration of the polymer and / or low molecular weight of the liquid crystal layer by expanding and blocking the region that could not be blocked due to the inevitable task of expressing natural colors in a display.
[0089] The near ultraviolet absorbing agent may be included in an amount of 0.01 to 5 parts by weight, preferably 0.1 to 1 part by weight, and more preferably 0.3 to 0.7 parts by weight, based on the total weight of the near ultraviolet protection layer composition.
[0090] The UV light enhancer absorbs UV light to block UV light, and transfers (absorbs and then releases) energy to an initiator contained in the hard coating composition through a photochemical reaction to promote hardening of the hard coating layer. Through such a series of photochemical reactions, the UV light enhancer maintains a low transmittance and simultaneously induces an initiation reaction of the initiator that causes a crosslinking reaction of the UV curable material. When the laminated film according to an embodiment of the present invention includes the UV light enhancer, the adhesion to the substrate can be improved. According to an embodiment of the present invention, the UV light enhancer may have a maximum absorption wavelength of 350 nm to 400 nm, preferably 355 nm to 395 nm, and more preferably 360 nm to 390 nm.
[0091] The ultraviolet light enhancer may be, for example, one or more selected from oxazole, anthraquinone, naphthoquinone, quinone, thioxanthone, acridone, benzoyldiphenylphosphine oxide, 1,2-diketone, phenothiazine, ketocoumarin, fluorene, naphthiazoline, biacetyl, benzyl and derivatives thereof, perylene, and substituted / unsubstituted anthracene. In terms of being able to effectively absorb ultraviolet light in the 350 to 400 nm region, an oxazole-based compound is preferred.
[0092] The ultraviolet light enhancer may be included in an amount of 0.01 to 5 parts by weight, preferably 0.1 to 2 parts by weight, and more preferably 0.5 to 1.5 parts by weight, based on the total weight of the near ultraviolet protection layer composition.
[0093] Second polarizing plate 110-2 The second polarizer 110-2 may have the same contents as the first polarizer 110-1, except that it may or may not include an ultraviolet blocking substrate and a near ultraviolet protection layer, and therefore the description thereof will be omitted.
[0094] In one or more embodiments, at least one of the first polarizer 110-1 and the second polarizer 110-2 may further include one or more functional layers selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjustment layer, and / or a refractive index adjustment layer.
[0095] The functional coating layer is provided to improve the hardness of the polarizing plate, and is not particularly limited as long as it can improve the hardness of the polarizing plate, and may include, for example, a hard coating layer and / or a low refractive index layer.
[0096] The hard coating layer composition may be formed from a hard coating composition including an acrylate-based or epoxy-based compound, inorganic fine particles, a photoinitiator, etc. The acrylate-based compound may include a monomer or oligomer including a (meth)acrylate group, and the term "(meth)acryl-" as used herein is used to mean "methacryl-", "acryl-", or both. Non-limiting examples of the acrylate-based compound include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate. Examples of the acrylate include bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, isooctyl (meth)acrylate, iso-dexyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, and isoborneol (meth)acrylate. These may be used alone or in combination of two or more. The acrylate compound may include an epoxy (meth)acrylate compound and / or a urethane (meth)acrylate compound.The epoxy compound may include a monomer or oligomer having at least one epoxy group in the molecule. The epoxy group may be an alicyclic epoxy group. The alicyclic ring included in the epoxy group may have 3 to 7 carbon atoms, for example, an alicyclic epoxy group including a cyclohexane ring (cyclohexyl epoxy). The alicyclic ring may have a substituent. For example, the alicyclic ring may include an alkyl substituent having 1 to 20 carbon atoms. If the alkyl substituent has more than 20 carbon atoms, it may be disadvantageous in terms of curing speed. The alkyl substituent may be a straight chain type or a branched type, and in the case of the branched type, the number of carbon atoms may be 3 or more. Meanwhile, in the method for producing a hard coating layer according to the present invention, in addition to the above-mentioned components, additives commonly used in the technical field to which the present invention belongs, such as a photoinitiator, a surfactant, an anti-yellowing agent, a labeling agent, and / or an antifouling agent, may further be included. In addition, the content of the additives is not particularly limited since it can be variously adjusted within a range that does not deteriorate the physical properties of the hard coating layer composition according to the present invention.
[0097] The low refractive index layer may be provided to improve the hardness of the polarizing plate within the scope of the present invention. The low refractive index layer may contain one or more low refractive index agents selected from the group consisting of SiO2, Al2O3, MgF2, CaF, and cryloite, and in some embodiments, may contain the compounds used in the hard coating layer and other resins commonly used in the technical field to which the present invention belongs. The hard coating layer and the low refractive index layer may be used alone, or in some embodiments, may be used as a multi-layer structure.
[0098] The functional coating layer may be formed on one surface of the polarizer in direct contact therewith, but is not limited thereto. For example, when the polarizing plate includes a retardation control layer and / or a refractive index control layer, the functional coating layer may be formed on one surface of the retardation control layer and the refractive index control layer, and the functional coating layer, the retardation control layer, the refractive index control layer, and the polarizer may be sequentially laminated.
[0099] The functional coating layer is preferably formed on the liquid crystal layer side of the polarizer, i.e., on the inside of the polarizer, but is not limited thereto, and may also be formed on the outside of the polarizer, and the polarizer, the functional coating layer, and the protective layer may be laminated in sequence. In this case, the functional coating layer has an advantage that it can minimize cracks or scratches generated during the manufacturing or processing process of the optical laminate by imparting a level of hardness suitable for forming members such as a transparent conductive layer on the polarizer.
[0100] The functional coating layer may have excellent abrasion resistance and may further improve the bending resistance and durability of the optical laminate, and more specifically, may more effectively suppress the occurrence of defects such as cracks in the conductive layer due to pressure application by a spacer during the bonding process of the optical laminate or chemical reactions of the liquid crystal, alignment film, etc.
[0101] In one or more embodiments, the functional coating layers may each have a dry thickness of 1 to 50 μm, more preferably 1 to 40 μm, but is not limited thereto.
[0102] The protective layer (not shown) serves to preserve the polarization characteristics of the polarizer from post-processing and external environments, and may be implemented in the form of a protective film, etc. The protective layer may be formed on one or both sides of the polarizer in direct contact therewith, but is not limited thereto. For example, the protective layer may be used as a multi-layer structure in which one or more protective layers are continuously stacked, or may be formed in direct contact with another member such as a retardation adjusting layer. In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).
[0103] The protective layer may further include an ultraviolet absorbing agent on the outermost surface to prevent deterioration of the optical laminate. The ultraviolet absorbing agent is not particularly limited as long as it is capable of preventing deterioration of the optical laminate due to ultraviolet rays, and examples of the ultraviolet absorbing agent include salicylic acid-based ultraviolet absorbing agents (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone-based ultraviolet absorbing agents (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole-based ultraviolet absorbing agents (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl)benzotriazole, etc.), and the like. 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and and side chain dodecyl)-4-methylphenol, a mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate ultraviolet absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of substrates such as polarizing plates, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,
[0104] The protective layer is intended to protect the polarization characteristics of the polarizing plate from post-processing and external environments, and may be implemented in the form of a protective film, etc. The protective layer may be used in a multi-layer structure in which one or more protective layers are continuously stacked, or may be used in combination with other functional layers.
[0105] In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).
[0106] The retardation control layer is for compensating for the optical properties of the optical laminate and may be implemented in the form of a retardation film, etc., and may be a conventional or later developed retardation film, etc. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light may be used, and these may be used alone or in combination.
[0107] The retardation control layer may be formed on one surface of the polarizer in direct contact therewith, but is not limited thereto. For example, the retardation control layer may be formed on one surface of the protective layer in direct contact therewith, or may be formed on one surface of the refractive index control layer in direct contact therewith.
[0108] The retardation control layer may be a polymer stretched film obtained by stretching a polymer film capable of imparting optical anisotropy by stretching in an appropriate manner, or a liquid crystal polymer film.
[0109] In one embodiment, the polymer stretched film may be a polymer layer including polyolefins such as polyethylene (PE) or polypropylene (PP), cycloolefin polymers (COP) such as polynorbornene, polyesters such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resins, polycarbonate (PC), polyethylene terephthalate (PET), polyacrylate, cellulose ester polymers such as polyvinyl alcohol (PVA) or triacetyl cellulose (TAC), or copolymers of two or more monomers among the monomers forming the polymers.
[0110] The method for obtaining the polymer stretched film is not particularly limited, and for example, the polymer material is molded into a film form and then stretched. The method for forming into the film form is not particularly limited, and it is possible to mold into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, cast molding, etc., and secondary processing molding methods such as compressed air molding and vacuum molding can also be used. Among them, extrusion molding and cast molding are preferably used. At this time, for example, an extrusion machine equipped with a T die, a circular die, etc. can be used to extrusion mold an unstretched film. When a molded product is obtained by extrusion molding, if a material in which various resin components, additives, etc. are melt-kneaded in advance can be used, it can also be molded through melt kneading during extrusion molding. In addition, various resin components can be dissolved using a solvent common to various resin components, such as chloroform, methylene dichloride, etc., and then cast-dried and solidified to cast-mold an unstretched film.
[0111] The polymer stretched film can be produced by uniaxially stretching the formed film in the mechanical direction (MD; mechanical direction, lengthwise or longitudinal direction) or uniaxially stretching the formed film in the transverse direction (TD; transverse direction, widthwise or transverse direction) of the mechanical direction. Alternatively, a biaxially stretched film can be produced by stretching the formed film using a sequential biaxial stretching method of roll stretching and tenter stretching, a simultaneous biaxial stretching method using tenter stretching, a biaxial stretching method using tubular stretching, or the like.
[0112] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be the same as that of the coating type polarizer.
[0113] In one or more embodiments, the thickness of the retardation control layer may be, but is not limited to, 10 to 100 μm in the case of a polymer stretched film in order to thin the optical laminate, and 0.1 to 5 μm in the case of a liquid crystal polymer film.
[0114] The refractive index adjustment layer is provided to compensate for the refractive index difference of the optical laminate due to the transparent conductive layer, and may serve to improve visibility by reducing the refractive index difference. The refractive index adjustment layer may also be provided to correct a hue caused by the transparent conductive layer. Meanwhile, when the transparent conductive layers 120-1 and 120-2 described below have a pattern, the refractive index adjustment layer can compensate for the transmittance difference between a patterned region where the pattern is formed and a non-patterned region where the pattern is not formed.
[0115] Specifically, the transparent conductive layer is laminated adjacent to another member having a different refractive index, and a difference in light transmittance may be induced due to the difference in refractive index between the adjacent layers. In particular, when a pattern is formed on the transparent conductive layer, a problem may occur in that the patterned region and the non-patterned region are visually distinguishable. Therefore, by including the refractive index control layer, the refractive index is compensated to reduce the difference in light transmittance of the optical laminate, and in particular, when a pattern is formed on the transparent conductive layer, the patterned region and the non-patterned region are visually distinguishable from each other.
[0116] In one embodiment, the refractive index of the refractive index adjustment layer may be appropriately selected depending on the material of the adjacent other member, and may be preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, it is possible to prevent light loss due to a sharp difference in refractive index between the other member and the transparent conductive layer. The refractive index adjustment layer is not particularly limited as long as it can prevent a sharp difference in refractive index between the other member and the transparent conductive layer, and may be a compound used to form a conventional or later developed refractive index adjustment layer, and may be formed from a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound, for example.
[0117] In addition to the above-mentioned functional layers, the polarizing plates 110-1 and 110-2 may further include other functional layers to supplement or enhance the properties of the polarizing plates, for example, an overcoat layer to further improve mechanical durability.
[0118] In one or more embodiments, the polarizers 110-1 and 110-2 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm, such that the polarizers 110-1 and 110-2 maintain their optical properties and allow for the manufacture of a thin optical laminate.
[0119] Transparent conductive layers (120-1 and 120-2) The transparent conductive layers 120-1 and 120-2 are provided for driving the liquid crystal layer 130 described below, and may be formed in direct contact with the polarizers. For example, as shown in Fig. 2, the first transparent conductive layer 120-1 and the second transparent conductive layer 120-2 may be formed in direct contact with the first polarizer 110-1 and the second polarizer 110-2, respectively.
[0120] Conventional optical laminates used in the manufacture of smart windows, etc., are manufactured by forming a conductive layer for driving liquid crystal on one side of a substrate and bonding the other side of the substrate with a polarizing plate. However, the variable transmittance optical laminate according to the present invention is characterized in that it does not include a separate substrate for forming a conductive layer, but directly forms a conductive layer on one side of a polarizing plate, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.
[0121] In one embodiment of the present invention, the first transparent conductive layer 120-1 and the second transparent conductive layer 120-2 may be formed by direct deposition on one surface of the polarizers 110-1 and 110-2. In this case, the transparent conductive layer may be formed by directly contacting the pre-treated surface of the polarizers after performing a pre-treatment such as a corona treatment or a plasma treatment on one surface of the polarizers in order to improve adhesion to the polarizers 110-1 and 110-2. The pre-treatment is not limited to a corona treatment or a plasma treatment, and any conventional or later developed pre-treatment process may be used within the scope of the present invention.
[0122] In another embodiment, the transparent conductive layers 120-1 and 120-2 may be formed in direct contact with the polarizer through an easy-adhesion layer (not shown) provided on one side of the polarizer in order to improve adhesion to the polarizer. The easy-adhesion layer may be made of the adhesive and / or pressure-sensitive adhesive material described in the adhesive layer among other members described later, but is not limited thereto.
[0123] The transparent conductive layers 120-1 and 120-2 preferably have a visible light transmittance of 50% or more, and may include, for example, one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires, but are not limited thereto, and any conventional or later developed transparent conductive layer material may be used.
[0124] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium zinc tin oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), fluorine tin oxide (FTO), zinc oxide (ZnO), etc. The metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of them, for example, a silver-palladium-copper (APC) alloy or a copper-calcium (CuCa) alloy. The carbon-based material may include at least one selected from the group consisting of carbon nanotubes (CNTs) and graphene, and the conductive polymer may include at least one selected from the group consisting of polypyrrole, polythiophene, polyacetylene, PEDOT, and polyaniline. The conductive ink may be an ink in which a metal powder and a curable polymer binder are mixed, and the nanowire may be, for example, a silver nanowire (AgNW).
[0125] In addition, the transparent conductive layers 110-2 and 120-2 may be formed into a two-layer structure by combining the above materials, for example, into a two-layer structure including a metal layer and a transparent conductive oxide layer to reduce the reflectance and increase the transmittance of incident light.
[0126] The transparent conductive layers 110-2 and 120-2 may be formed by a method commonly used in the art, for example, a coating process such as spin coating, roller coating, bar coating, dip coating, gravure coating, curtain coating, die coating, spray coating, doctor coating, and kneader coating; a printing process such as screen printing, spray printing, inkjet printing, relief printing, intaglio printing, and planographic printing; and a deposition process such as CVD (chemical vapor deposition), PVD (physical vapor deposition), and PECVD (plasma enhanced chemical vapor deposition).
[0127] Liquid crystal layer 130 The liquid crystal layer 130 can change the driving mode of the optical stack by controlling the transmittance of light incident from one or more directions by an electric field.
[0128] The liquid crystal layer 130 may include a liquid crystal compound and may be located, for example, in a space provided by a sealant layer (not shown) and a spacer (not shown) provided between the first polarizer 110-1 and the second polarizer 110-2 in the light control region.
[0129] The liquid crystal layer 130 is characterized by being driven by an electric field. The liquid crystal layer 130 may be located between the first polarizer 110-1 and the second polarizer 110-2 located in the light control region of the optical laminate 100. In one embodiment, the liquid crystal layer 130 may be located in a space provided by a sealant (not shown) and a spacer (not shown) provided between the first polarizer 110-1 and the second polarizer 110-2 in the light control region. In addition, the liquid crystal layer 130 may adjust the transmittance of light incident from an external light source by an electric field formed between the first transparent conductor 120-1 or the second transparent conductor 120-2.
[0130] The liquid crystal layer 130 may be driven by a conventional or later developed liquid crystal behavior mode, for example, a twisted nematic (TN) mode, a super twisted nematic (STN) mode, or the like.
[0131] According to another embodiment of the present invention, the liquid crystal layer 130 may include one or more spacers selected from the group consisting of ball spacers and column spacers. In particular, a ball spacer is preferable. The number of ball spacers may be one or more, and the ball spacer preferably has a diameter of 1 to 10 μm. In addition, when viewed in a planar direction, the area of the ball spacer in the liquid crystal layer 110 (i.e., the light control region) is preferably 0.01 to 10% of the area of the liquid crystal layer 130 in terms of improving the user's visibility and the transmittance in the light transmission mode, but is not limited thereto.
[0132] others In one embodiment, the liquid crystal layer 130 may further include other components within the scope of the present invention, for example, a sealant, an alignment film, an adhesive layer, and / or an ultraviolet absorbing layer, which may be formed on both sides of the liquid crystal layer 130 containing the liquid crystal compound.
[0133] The sealant may include a curable resin as a base resin. The base resin may be a UV-curable resin or a thermosetting resin known in the art to be used for sealants. The UV-curable resin may be a polymer of a UV-curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.
[0134] The base resin of the sealant may be, for example, an acrylate-based resin, an epoxy-based resin, a urethane-based resin, a phenol-based resin, or a mixture of the resins. In one embodiment, the base resin may be an acrylate-based resin, and the acrylate-based resin may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a polyfunctional acrylate. In another embodiment, the sealant may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate may mean a compound having one acrylic group, and a polyfunctional acrylate may mean a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately performed within a range that does not impair the object of the present application. The sealant may further include an initiator, for example, a photoinitiator or a thermal initiator, as necessary.
[0135] The sealant may be formed by a method commonly used in the art, for example, by drawing the sealant onto the outer periphery (i.e., non-active area) of the liquid crystal layer using a dispenser equipped with a nozzle.
[0136] The alignment film is not particularly limited as long as it is capable of imparting alignment to the liquid crystal compound. For example, the alignment film may be fabricated by applying and curing an alignment film coating composition including an alignment polymer, a photopolymerization initiator, and a solvent. The alignment polymer is not particularly limited, and may be a polyacrylate resin, a polyamic acid resin, a polyimide resin, a polymer including a cinnamate group, or a conventional or later developed polymer capable of exhibiting alignment.
[0137] The adhesive layer may be formed using an adhesive or pressure-sensitive adhesive, and preferably has an appropriate adhesive strength so as to prevent peeling, air bubbles, etc. from occurring when the optical laminate is handled, as well as transparency and thermal stability.
[0138] The adhesive may be a conventional or later developed adhesive, for example, a photocurable adhesive, which exhibits strong adhesive strength by crosslinking and curing when exposed to active energy rays such as ultraviolet (UV) or electron beam (EB), and may be composed of a reactive oligomer, a reactive monomer, a photopolymerization initiator, etc.
[0139] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a polymer bond by photopolymerization to form a hardened coating. Usable reactive oligomers include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, etc.
[0140] The reactive monomer functions as a crosslinking agent and a diluent for the reactive oligomer, and affects the adhesive properties. Usable reactive monomers include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.
[0141] The photopolymerization initiator absorbs light energy to generate radicals or cations to initiate photopolymerization, and may be selected from those suitable for the photopolymerizable resin.
[0142] The adhesive may be a conventional or later developed adhesive, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity, but in terms of availability, etc., it may be preferably an acrylic adhesive, and may contain, for example, a (meth)acrylate copolymer, a crosslinking agent, and a solvent.
[0143] The crosslinking agent may be a conventional or later developed crosslinking agent, and may include, for example, a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a methylol polymer, or the like, and preferably includes a polyisocyanate compound.
[0144] The solvent may include a typical solvent used in the field of resin compositions, such as alcohol compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. These may be used alone or in combination of two or more.
[0145] The thickness of the adhesive layer may be appropriately determined depending on the type of resin acting as an adhesive, adhesive strength, environment in which the adhesive is used, etc. In one embodiment, the adhesive layer may have a thickness of 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm in order to ensure sufficient adhesive strength and minimize the thickness of the optical laminate, but is not limited thereto.
[0146] The ultraviolet absorbing layer is not particularly limited as long as it is for further preventing deterioration of the optical laminate due to ultraviolet rays, and examples thereof include salicylic acid-based ultraviolet absorbers (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone-based ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole-based ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dimethoxybenzophenone, etc.), and the like. -tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(dichlorophenyl)-1,2-diphenyl-2-propanediol, (chain and side chain dodecyl)-4-methylphenol, mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate ultraviolet absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of the polarizing plate and the transmittance variable layer, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,
[0147] <Method of Manufacturing Variable Transmittance Optical Laminate> The present invention includes the above-described method for producing the variable transmittance optical laminate. The method for producing the variable transmittance optical laminate is not particularly limited, and the optical laminate can be produced using any bonding technique or the above-described photolithography technique.
[0148] For example, the conductive layer of the polarizing plate can be formed by coating a composition for forming a functional conductive layer on a triacetyl cellulose film or a cycloolefin polymer (COP) and then bonding it to a polyvinyl alcohol-based polarizer. Alternatively, the polarizing plate can be formed by selectively coating a functional conductive layer composition on the triacetyl cellulose film or the cycloolefin film surface of the polarizing plate, which is manufactured by bonding a triacetyl cellulose film or a triacetyl cellulose film and a cycloolefin film to both sides of a polyvinyl alcohol-based polarizer (23 μm, KURARAY) using an adhesive.
[0149] <Smart Window> In addition to the optical laminate, the present invention includes a smart window including the optical laminate. The present invention also includes an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition, and a building fixture including the smart window.
[0150] The automobile including the smart window of the present invention may be manufactured by bonding vehicle glass to both sides of an optical laminate including a liquid crystal layer and an optical functional layer using a pressure-sensitive adhesive. For example, the automobile may be manufactured by placing an adhesive film and vehicle glass on both sides of the optical laminate, and then heating for 10 to 20 minutes at a temperature of 90°C and about 1 bar or in a vacuum state using a press machine, or by coating a resin on one side of the vehicle glass, vacuum bonding the vehicle glass to both sides of the optical laminate, and UV curing the resin. The adhesive film may include an EVA (ethylene vinyl acetate) film, a PVB (polyvinyl butyral) film, etc., and the resin may be a resin having a storage modulus (G') of 10 3 or 10 5 It may also contain OCR resin, etc.
[0151] In addition, the optical laminate may have building fixtures (glass for fixtures) bonded to one or both sides thereof, or may have glass for fixtures bonded to one side of the optical laminate by a lamination method to produce a smart window product for fixtures, or may have glass for fixtures bonded to both sides of the optical laminate by applying a UV adhesive and then curing with UV to produce a smart window product for fixtures. EXAMPLES
[0152] In the following, experimental examples including specific examples and comparative examples will be presented to aid in understanding the present invention. However, these are merely illustrative of the present invention and are not intended to limit the scope of the appended claims. It will be apparent to those skilled in the art that various changes and modifications to the examples are possible within the scope and technical spirit of the present invention, and it is to be understood that such changes and modifications fall within the scope of the appended claims.
[0153] Preparation Example 1: Preparation of near-ultraviolet protection layer composition 50.8 parts by weight of hexafunctional urethane acrylate (Kyoeisha, UA-306I), 44.6 parts by weight of butyl acetate, 3.3 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.3 parts by weight of silicone labeling agent (BYK, BYK-UV3530), 0.5 parts by weight of near-ultraviolet absorber (FDB-009 (λmax=402nm), Yamada Co., Ltd.), and 0.5 parts by weight of ultraviolet ray increase / decrease agent (NF-NA-01 (λmax=379nm), Nippon Chemical Works Co., Ltd.) were mixed using a stirrer and filtered using a PP filter to produce a near-ultraviolet protective layer composition.
[0154] Manufacturing Example 2: Manufacturing of the first polarizing plate The following steps (1) to (7) were carried out in order to produce a first polarizing plate.
[0155] (1) Swelling treatment process As the raw film, a 60 μm thick polyvinyl alcohol (PVA) film (Kuraray Co., Ltd., Kuraray Poval Film VF-PE#6000, average polymerization degree 2400, saponification degree 99.9 mol%) was continuously unwound from a raw roll and transported, and immersed in a swelling bath containing pure water at 20° C. for 30 seconds. Next, stretching between the rolls (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip rolls. The stretching ratio based on the raw film was 2.5 times.
[0156] (2) Dyeing process The film that had passed through the nip rolls in (1) was immersed in a dye bath at 30° C. containing pure water: potassium iodide: iodine: boric acid in a mass ratio of 100:2:0.01:0.3 for 120 seconds. Next, the film was stretched between the rolls (longitudinal uniaxial stretching) with a difference in peripheral speed between the nip rolls. The stretching ratio based on the film after the swelling treatment step was 1.1 times.
[0157] (3) Crosslinking process The film that had passed through the nip rolls in (2) was immersed in a first crosslinking bath at 56° C., containing pure water: potassium iodide: boric acid in a mass ratio of 100:12:4, for 70 seconds. The film was stretched between the rolls (longitudinal uniaxial stretching) with a difference in peripheral speed between the nip rolls and a nip roll provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was 1.9 times, based on the film after the dyeing process.
[0158] (4) Complementary color processing process The crosslinked film was immersed for 10 seconds in a second crosslinking bath at 40° C. containing pure water:potassium iodide:boric acid in a mass ratio of 100:9:2.9.
[0159] (5) Cleaning process After the second crosslinking treatment, the film was immersed in pure water at 14°C in a cleaning bath for 5 seconds, and the shower volume was 5 m 3 / h and shower temperature 14°C.
[0160] (6) Drying process The washed film was passed through a drying oven at 80° C. for 190 seconds in order to heat-dry it. After heat-drying, the polarizer film had a moisture content of 13.6% and a thickness of about 21 μm.
[0161] (7) Joining process A water-based adhesive containing 5 parts by mass of PVA per 100 parts by mass of water was prepared. A UV-blocking substrate (80 μm, TAC film, manufactured by HYOSUNG) and a protective film (80 μm, ZRT film, manufactured by HYOSUNG) were laminated on both sides of the polarizer film obtained in (6) above using the water-based adhesive. The resulting laminate was exposed to UV light to harden the adhesive, producing a first polarizing plate. The thickness of the adhesive layer after UV exposure was about 2 μm.
[0162] Manufacturing Example 3: Formation of near-ultraviolet protection layer The near ultraviolet protection layer composition of Preparation Example 1 was cured on the polarizing plate of Preparation Example 2, and then coated to a thickness of 6 μm. The solvent was dried, and the UV integrated light amount was 500 mJ / cm 2 in a nitrogen atmosphere. 2 is irradiated to form a near ultraviolet protection layer.
[0163] Production Example 4: Vapor Deposition of First Transparent Conductive Layer - Production of First Laminate The first polarizing plate having the near-ultraviolet protection layer formed thereon, obtained in Preparation Example 3, was inserted, 450 W DC power was applied to operate the sputtering gun, and plasma was then induced in the ITO (10 wt% Sn doped In2O3) target to form a 40 nm thick transparent conductive layer (ITO layer) on the near-ultraviolet protection layer. The ion gun was operated with 50 W DC power to ionize the transparent conductive layer to manufacture a first laminate including the first polarizing plate and the first transparent conductive layer. At this time, the pressure at room temperature was maintained at 3 mTorr, and argon gas and oxygen gas were supplied at 30 sccm and 1 sccm, respectively.
[0164] Production Example 5: Production of second laminate A second laminate including a second polarizing plate and a second transparent conductive layer was prepared in the same manner as in Preparation Examples 2 and 4, except that the ultraviolet blocking substrate and the near ultraviolet protection layer were not included.
[0165] Manufacturing Example 6: Formation of alignment film An alignment solution (RN-4662, Nissan Chemical Industries, Ltd.) was coated on the first transparent conductive film obtained in Preparation Example 4 and the second transparent conductive film obtained in Preparation Example 5, and then dried at 80° C. for 2 minutes. Then, the dried alignment solution was irradiated with UV light to form an alignment film.
[0166] Manufacturing Example 7: Spreading ball spacers First, 0.03 g of ball spacers (SP series, manufactured by SEKISUI) was mixed with 100 ml of isopropyl alcohol (IPA) to prepare a mixed solvent. Next, the second laminate of Manufacturing Example 5 was placed in a spacer sprayer (SDSS-KHU02, manufactured by Shindo Eng Lab), and the mixed solvent was sprayed at 110°C. After that, it was dried for 20 minutes to form ball spacers on the alignment film.
[0167] Manufacturing Example 8: Formation and bonding of sealant and liquid crystal layer - manufacturing of variable transmittance optical laminate On the second transparent conductive layer of the second laminate on which the alignment film was formed in Manufacturing Example 6, a sealant with a viscosity of 250,000 mPa·s (Photolec S, manufactured by SEKISUI) was applied at a discharge pressure of 200 mPa using a sharp needle (PN-17G, manufactured by MUSASHI) and a sealant dispenser (SHOTmini 200Ωx, manufactured by MUSASHI) so that the sealant would sink into the recesses. Liquid crystal was injected onto the alignment film of the second laminate by a drop method (One Drop Filling: ODF). Next, the alignment films of the first polarizer and the second polarizer were arranged parallel to each other at 0° or 90°, and the first laminate and the second laminate were heated with a pressure of 3 kg / cm. 2 After bonding with pressure, UV curing (500 mJ / cm) was performed along the sealant line. 2 ) was carried out to produce a variable transmittance optical laminate.
[0168] Example 1 The variable transmittance optical laminate of Production Example 8 was applied to Example 1.
[0169] Example 2 A variable transmittance optical laminate was manufactured in the same manner as in Example 1, except that in the first polarizer, the protective layer was positioned on the opposite side to the liquid crystal layer, and a transparent conductive layer was formed on the UV blocking substrate.
[0170] Comparative Example 1 In the (7) bonding process of Preparation Example 2, a protective film (80 μm ZRT film (TAC film, not UV-TAC (ultraviolet ray blocking substrate)), manufactured by HYOSUNG) was used instead of the ultraviolet ray blocking substrate, and a variable transmittance optical laminate having the same structure as that of Example 1 was manufactured, except that a separate near-ultraviolet ray protective layer was not included.
[0171] The structures of the variable transmittance optical laminates of Example 1, Example 2, and Comparative Example 1 are summarized in Table 1 below.
[0172] [Table 1]
[0173] Experimental Example (1) Evaluation of light resistance The variable transmittance optical laminates according to the examples and comparative examples were manufactured, and arranged in the following order: light source / 2.0T soda lime glass / variable transmittance optical laminate. The UV blocking substrate of the first polarizing plate of the variable transmittance optical laminate based on Example 1 was oriented toward the outer surface, i.e., the light source, and light was irradiated under the following conditions.
[0174] -Light source used: Carbon Arc Lamp-type -Irradiance: 500W / m 2 (Wavelength: 300nm to 700nm) -Test time: 1500 hours -Temperature: 70℃ The opaque state (voltage on) after the above-mentioned light fastness conditions was observed, and the light fastness was evaluated according to the following criteria, and the results are shown in Table 1 above.
[0175] <Evaluation criteria> ○: Maintains opaque state (Figure 3a) △: Some light leakage was confirmed (Figure 3b). X: Light leakage confirmed over the entire surface (Figure 3c) Referring to the experimental data in Table 1, in the case of the embodiment in which the first polarizer of the first laminate includes the UV blocking substrate and the near UV protective layer, the light leakage phenomenon was hardly observed during the light resistance evaluation, compared to the comparative example in which the light leakage phenomenon was observed over the entire surface because the UV blocking substrate and the near UV protective layer were not included (see FIG. 3c). In particular, compared to the embodiment in which the near UV protective layer was located on the outer surface facing the light source (see FIG. 3b), the embodiment in which the UV blocking substrate was located on the outer surface and the UV blocking substrate, polarizer, and near UV protective layer were sequentially laminated did not experience any light leakage phenomenon even when a voltage was applied, and maintained an opaque state, showing better results in the light resistance evaluation (see FIG. 3a).
[0176] Therefore, the variable transmittance optical laminate of the present invention prevents deterioration of the liquid crystal layer due to ultraviolet rays, and by including the variable transmittance optical laminate, a high-quality smart window can be provided. [Explanation of symbols]
[0177] 100: Variable transmittance optical laminate 110-1: First polarizing plate 111: UV blocking base material 112: Polarizer 113: Near UV protection layer 120-1: First transparent conductive layer 110-2: Second polarizing plate 120-2: Second transparent conductive layer 130: Liquid crystal layer A: Light source
Claims
1. A first polarizing plate; a first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate facing the first polarizing plate; a second transparent conductive layer formed on one surface of the second polarizing plate and facing the first transparent conductive layer; A variable transmittance optical laminate comprising: a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer; The first polarizing plate is a variable transmittance optical laminate including an ultraviolet blocking substrate, a polarizer, and a near ultraviolet protection layer.
2. The variable transmittance optical laminate according to claim 1 , wherein the first polarizing plate is formed on an outer surface facing a light source.
3. The variable transmittance optical laminate according to claim 2, wherein the first polarizing plate is formed by sequentially stacking an ultraviolet blocking substrate, a polarizer, and a near ultraviolet protection layer on an outer surface facing a light source.
4. The variable transmittance optical laminate according to claim 1 , wherein the ultraviolet ray blocking substrate has a transmittance of 10% or less at a wavelength of 380 nm or less.
5. The variable transmittance optical laminate according to claim 1 , wherein the ultraviolet blocking substrate comprises an ultraviolet blocking additive.
6. The variable transmittance optical laminate according to claim 1 , wherein the ultraviolet ray blocking substrate comprises at least one selected from the group consisting of a polyester film, a cellulose film, a polyimide film, and a polycarbonate film.
7. The variable transmittance optical laminate according to claim 1 , wherein the near-ultraviolet protection layer comprises at least one selected from the group consisting of a near-ultraviolet absorber and an ultraviolet light enhancer.
8. The variable transmittance optical laminate according to claim 7, wherein the near-ultraviolet absorbing agent has a maximum absorption wavelength of 390 nm to 430 nm.
9. The variable transmittance optical laminate according to claim 8 , wherein the near-ultraviolet absorbing agent is a cyanine compound.
10. The variable transmittance optical laminate according to claim 7, wherein the ultraviolet light enhancer has a maximum absorption wavelength of 350 nm to 400 nm.
11. The variable transmittance optical laminate according to claim 10, wherein the ultraviolet light enhancer is an oxazole-based compound.
12. 2. The variable transmittance optical laminate according to claim 1, wherein at least one of the first polarizing plate and the second polarizing plate includes one or more functional layers selected from the group consisting of a functional coating layer, a protective layer, a phase difference control layer, and a refractive index control layer.
13. The variable transmittance optical laminate of claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm.
14. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizer and the second polarizer without a separate substrate between the transparent conductive layer and the first polarizer and the second polarizer.
15. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer further includes an easy-adhesion layer between the first polarizing plate and the second polarizing plate and is formed in direct contact with the first polarizing plate and the second polarizing plate.
16. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises at least one selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
17. The variable transmittance optical laminate according to claim 1, wherein the liquid crystal layer includes at least one spacer selected from the group consisting of a ball spacer and a column spacer.
18. The variable transmittance optical laminate according to claim 1 , further comprising at least one layer selected from the group consisting of a sealant, an alignment film, an adhesive layer, and an ultraviolet absorbing layer.
19. A method for producing the variable transmittance optical laminate according to claim 1 .
20. A smart window comprising the variable transmittance optical stack according to any one of claims 1 to 18.
21. 21. A mode of transportation comprising the smart window of claim 20.
22. 21. A car comprising the smart window according to claim 20 applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
23. A wearable device comprising the smart window of claim 20.
24. 21. An architectural fixture comprising the smart window of claim 20.
Citation Information
Patent Citations
Polarizing film having ultraviolet absorption performance and manufacturing method thereof
KR100416924B1
Cited By
Electronic component
CN121862600A
